2022
DOI: 10.1021/acscatal.2c02261
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy Tuning on Cu/NC Catalysts for CO Electroreduction

Abstract: Electrochemical CO reduction reaction (CORR) represents a potential approach to generate value-added products. Nonetheless, it is generally challenging for conventional measurements to quantify the catalytic surface properties, due to the geometric blockage and synergistic effect from the support. Herein, the surface energy of copper-loaded nitrogen-doped carbon (Cu/NC) was investigated by adsorption with specific functional groups using inverse gas chromatography (IGC). The dispersive component (γS D) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…For instance, Sargent and coworkers reported a polymer-based gas diffusion electrode with an abrupt interface between Cu catalyst, graphite, and porous polytetrafluoroethylene, 51 achieving an efficient CO 2 -to-C 2 H 4 conversion (FE ∼ 70%) and a high CO 2 RR durability of 150 h in 7 M KOH. Another recent study 34 by Liu et al based on Cu catalyst loaded on different nitrogen-doped carbon supports (with different atomic ratios of N in those supports) demonstrated that surface energy (or local acid−base property) also plays a significant role in CORR. The surface energy analysis suggested that the Cu/N 0.17 C catalyst with the highest basic parameter (K D = 7.350, Figure 4B) and optimal acid interaction (K A /K D ∼ 0.046, Figure 4C) exhibited the best catalytic performance in the CO-to-acetate conversion, and a FE of 63% was obtained at a partial current density of −330 mA•cm −2 (Figure 4D).…”
Section: Other Interfacial Microenvironmental Adjustments In Aqueous ...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Sargent and coworkers reported a polymer-based gas diffusion electrode with an abrupt interface between Cu catalyst, graphite, and porous polytetrafluoroethylene, 51 achieving an efficient CO 2 -to-C 2 H 4 conversion (FE ∼ 70%) and a high CO 2 RR durability of 150 h in 7 M KOH. Another recent study 34 by Liu et al based on Cu catalyst loaded on different nitrogen-doped carbon supports (with different atomic ratios of N in those supports) demonstrated that surface energy (or local acid−base property) also plays a significant role in CORR. The surface energy analysis suggested that the Cu/N 0.17 C catalyst with the highest basic parameter (K D = 7.350, Figure 4B) and optimal acid interaction (K A /K D ∼ 0.046, Figure 4C) exhibited the best catalytic performance in the CO-to-acetate conversion, and a FE of 63% was obtained at a partial current density of −330 mA•cm −2 (Figure 4D).…”
Section: Other Interfacial Microenvironmental Adjustments In Aqueous ...mentioning
confidence: 99%
“…(D) Faradaic efficiencies of C 1 and C 2+ at around −1.02 V vs RHE and corresponding ratios of C 2+ to C 1 products. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Recent Developments Of Cu-based Catalysts On Interfacial Mic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the catalyst support can also influence product selectivity. Recent studies suggest that N-doped carbon supports can stabilize Cu in a Cu–N coordination environment during electrolysis and shows the product selectivity toward ethanol or other C2 products. Cu on N-doped carbon has also been used in thermal catalysis and shows enhanced stability, and there are reports utilizing N-doped carbon as a catalyst support for electrocatalysis. A theoretical study of Cu dimer on C 2 N predicts a favored product of C 2 H 4 . We hypothesize that the N-doped carbon support for CO 2 RR will stabilize the intermediate states of CO 2 adsorbates and the catalysts, which leads to specific CO 2 RR products, owing to the coordination between the N and the d-orbitals of the metal atoms.…”
Section: Introductionmentioning
confidence: 95%
“… 30 36 Cu on N-doped carbon has also been used in thermal catalysis and shows enhanced stability, 37 and there are reports utilizing N-doped carbon as a catalyst support for electrocatalysis. 38 47 A theoretical study of Cu dimer on C 2 N predicts a favored product of C 2 H 4 . 48 We hypothesize that the N-doped carbon support for CO 2 RR will stabilize the intermediate states of CO 2 adsorbates and the catalysts, which leads to specific CO 2 RR products, owing to the coordination between the N and the d-orbitals of the metal atoms.…”
Section: Introductionmentioning
confidence: 99%